Extracellular vesicle-derived microRNAs in renal cell carcinoma: biological roles and clinical applications - He, Jiahui; Wang, Lanfeng; Yu, Bingqing; Huang, Wengbin; Ouyang, Chen; Zhou, Mingcan; Hu, Rong; Chen, Zhiping (Frontiers in Cell and Developmental Biology, 2025)
Renal cell carcinoma (RCC) is a common malignant tumour of the urinary system, characterised by high heterogeneity and a tendency to metastasise, with poor prognosis in advanced patients. Although surgical resection and targeted therapies such as tyrosine kinase inhibitors and immune checkpoint inhibitors have significantly improved survival outcomes in some patients, drug resistance and recurrence remain clinical challenges. In recent years, extracellular vesicles (EVs) and the microRNAs (miRNAs) they carry have emerged as a research hotspot due to their critical roles in tumour initiation, progression, immune regulation, and drug resistance. This systematic review summarises the biological functions of EVs-derived miRNAs in renal cell carcinoma and their potential applications in clinical diagnosis and treatment, with a focus on their value in diagnosis, prognosis, immune regulation, and prediction of treatment response.